Pigeon Pea [Cajanus cajan (L.) Millsp.] Seed Meal in Layer Diets: 1. Performance of Point of Lay Pullets Fed Raw or Processed Pigeon Pea Seed Meal Diets - Amaefule, K.U.; Ironkwe, M.C.; Obioha, F.C. (International Journal of Poultry Science, 2006)
Performance of point of lay black Bovan Nera pullets fed raw or processed pigeon pea seed meal (PSM) diets was determined with 150 (20 week old) pullets. They have not been fed any PSM diet before the study. The seeds (brown colored) were used as raw or processed (toasted for 30 minutes, boiled for 30 minutes, or soaked in water for 24 hours), all of which were milled. Each treatment had three replicates; each replicate had 10 birds in a completely randomized design (CRD). The experimental diets were isoenergetic and isonitrogenous. Measurements were feed intake, live weight, hen-day and hen-housed egg production, mortality, age at 1st, 25 and 50% egg production, external and internal egg quality characteristics. Raw PSM diet fed to point of lay pullets (POL) significantly (P< 0.05) improved hen-day production (67.79%), feed intake (101.50 g), and lowered age at 50% egg production (180.67 d) more than other diets. Layers fed toasted PSM diet laid eggs with superior weight (66.17 g), width (4.51 cm) and the lowest shell weight (4.37 g). Also layers fed toasted PSM diet laid eggs with superior albumen (11.87 mm) and yolk (20.50 mm) heights, albumen weight (45.80 g), albumen + yolk weight (61.60 g) and significantly (P< 0.05) higher Haugh unit (123.63) than the rest. It was concluded that 30% raw, toasted or soaked PSM diet could be fed to point of lay pullets without adverse effect on egg production, external and internal egg quality characteristics.